Promoting prenatal health care in poor rural areas through conditional cash transfers : evidence from JUNTOS in Peru - Díaz, Juan José (2017)
We assess the effects of JUNTOS, a conditional cash transfer program targeted to poor rural households in Peru, on the utilization of prena-tal health care by women exposed to the program during their most recent pregnancy. We implement a difference-in-differences estima-tion technique to uncover the effects of JUNTOS on the utilization of prenatal health care, the quality of prenatal health care, utilization of health care at birth, and obstetric complications at birth. We use data from the publicly available Demographic and Health Surveys (DHS) from the period 2000-2014. Our results suggest that the pro-gram has increased prenatal health care utilization. Even more salient, our results also suggest an improvement in the quality of health care received and a reduction of obstetric complications at birth.